2020
DOI: 10.1007/s10654-020-00648-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of periodontal disease on risk of dementia: a systematic literature review and a meta-analysis

Abstract: Objective: Periodontal disease (PD) is common and increases cardiovascular diseases. However, it is unclear whether PD is associated with increased risk of dementia. We carried out a systematic review and meta-analysis to investigate the influence of PD on dementia. We projected the number of dementia cases to be saved by reducing PD prevalence in the world. Method:We searched cohort and case-control studies reporting the association of PD with all dementia (or any specific type of dementia) through PubMed, ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 52 publications
5
45
1
1
Order By: Relevance
“…The role of sIgA as an immunoglobulin involved in protecting the oral mucosa and, consequently, its relationship with oral infections and inflammatory processes is known [41]. Recent studies also report an association between periodontal diseases and dementia processes [42][43][44]. However, we cannot demonstrate that this relationship occurs in our study because no periodontal diseases were identified in the subjects studied.…”
Section: Discussioncontrasting
confidence: 56%
“…The role of sIgA as an immunoglobulin involved in protecting the oral mucosa and, consequently, its relationship with oral infections and inflammatory processes is known [41]. Recent studies also report an association between periodontal diseases and dementia processes [42][43][44]. However, we cannot demonstrate that this relationship occurs in our study because no periodontal diseases were identified in the subjects studied.…”
Section: Discussioncontrasting
confidence: 56%
“…Interest has grown in the association among tooth loss, periodontal disease and dementia [ 21 , 24 ]. Tooth loss is a common indicator of poor oral health [ 20 ].…”
Section: Oral Health Of Elderly People With Alzheimer’s Diseasementioning
confidence: 99%
“…Neurological conditions have been associated with periodontitis, such as Alzheimer’s Disease, dementia, or PD [ 5 , 9 , 28 , 29 ]. From a biological standpoint, the association of periodontitis with these intricate illnesses may be based on the influence of systemic inflammation and the systemic spreading of periodontal pathogens products with potential affection of brain tissues [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%